UI / UX Website Moslem Hanania - Chairunnisa Fadhilla; Eko Purnomo (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2024)
The rapid and easy access to internet technology has also increased the popularity of Muslim fashion. The easier access to the internet, affects the increase in social media users from various socio-economic backgrounds, education levels and ages, as well as the fashion industry which is no longer intended only for certain elites. Moslem Hanania is a brand that sells Muslim clothing products for women that has offline and online stores. Moslem Hanania was founded in 2019 in Jakarta. The online sales process is currently most often used, namely through WhatssApp and Shopee, the obstacle felt by the owner at this time is that the product introduction and marketing activities are deemed less than optimal. If you only rely on existing online shopping applications, the obstacle is in competition and potential customers will not focus on the products you have. The second obstacle is that the owner wants to focus more on online sales but wants to have its own characteristics in online sales, the owner wants in online sales, the brand has its own website. The UI/UX design of the Moslem Hanania Website uses the Design Thingking method, so it can be concluded that this design is a problem that comes from a sense of empathy, the need for a solution to an existing problem, then continues to test for improvement.